2000
DOI: 10.1088/0953-8984/12/40/310
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Peierls instability in a quantum spin chain with Dzyaloshinskii-Moriya interaction

Abstract: We analysed the ground state energy of some dimerized spin-1 2 transverse XX and Heisenberg chains with Dzyaloshinskii-Moriya (DM) interaction to study the influence of the latter interaction on the spinPeierls instability. We found that DM interaction may act either in favour of the dimerization or against it. The actual result depends on the dependence of DM interaction on the distortion amplitude in comparison with such dependence for the isotropic exchange interaction.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 31 publications
(76 reference statements)
2
22
0
Order By: Relevance
“…40 The XX chain with the DM term is also exactly solvable within this context. [41][42][43][44] Thus, starting with the Hamiltonian (2.1) with = 0 and performing a Jordan-Wigner transformation to free fermions, …”
Section: A Free-fermion Casementioning
confidence: 99%
“…40 The XX chain with the DM term is also exactly solvable within this context. [41][42][43][44] Thus, starting with the Hamiltonian (2.1) with = 0 and performing a Jordan-Wigner transformation to free fermions, …”
Section: A Free-fermion Casementioning
confidence: 99%
“…The threshold value b c can be obtained by letting the variation qm p =qD ¼ 0 ðDa0Þ; and in the nonadiabatic case, b c is determined by a set of values of D; l and o p . If b c was simply a constant as previous works predicted [21], lm p would not change with D when b ¼ b c . However, in view of the determination of m p by D, b, l and o p , one might wonder why the DM interaction should have no effect on dimerization when b ¼ b c .…”
Section: (A)-(c)mentioning
confidence: 75%
“…The antisymmetric character of DM interaction is expressed by two principal cases, the uniform [18,19] and the staggered DM interactions [17,19,20], and has been studied by many previous authors. A numerical calculations of the groundstate energy of the spin-Peierls XX model and Heisenberg chain with DM interaction by Derzhko et al [21] found that uniform DM interaction may act against the dimerization but staggered DM interaction may act in favor of the dimerization. However, whether the staggered DM interaction always enhances the dimerization or the uniform DM interaction always acts against the dimerization has not been clearly answered.…”
mentioning
confidence: 99%
See 2 more Smart Citations